Liquid Tempeh Wastewater and EM4: A Combined Approach to Enhance Chilli Seed Germination (Journal of Environmental Microbiology and Toxicology, 2024)
Tempeh liquid wastewater, a by-product of tempeh production, is increasingly recognized as a potential liquid fertilizer. However, research on its fermentation into fertilizer is limited. This study aimed to enhance tempeh wastewater-derived fertilizer using effective microorganisms 4 (EM4) and evaluate its impact on chili seed germination. Two sets of organic fertilizers were prepared, including three controls and three treatments. Controls were 100% distilled water, 10% EM4 with 90% distilled water, and 100% tempeh wastewater, while treatments varied in tempeh wastewater and EM4 concentrations. Chemical analysis revealed variations in total carbon, salinity, phosphorus, and potassium, with undetectable nitrogen content in all formulations. Formulations with 25% tempeh wastewater had lower salinity, phosphorus, and potassium than those with 75% tempeh wastewater. The effects on chili seed germination showed that formulation A3 (25% tempeh wastewater and 10% EM4) resulted in significantly higher germination percentage, mean daily germination, seedling length, and vigor index compared to controls and higher tempeh wastewater formulations. Overall, 25% tempeh wastewater formulations demonstrated superior germination and growth, suggesting tempeh liquid fertilizer as an eco-friendly and effective option for chili cultivation. Further research is needed to optimize its composition and application in agriculture.
Keywords: Tempeh; Wastewater; EM4; Chili seed; Germination